MODELING OF TURBULENT FLOWS AROUND GROUND TRANSPORT VEHICLES USING HYBRID APPROACHES - Sokhatskyi, A. V. (Systems and Technologies, 2026)
The practical application of Direct Numerical Simulation (DNS) and Large Eddy Simulation (LES) is associated with a number of problems. These include insufficient computing power and a number of methodological issues. Over the past decades, models of turbulent flows have appeared that involve the simultaneous use of the LES method and Reynolds-averaged Navier-Stokes equations (RANS). These are the so-called hybrid RANS-LES models. The use of hybrid approaches simplifies the solution of certain aerodynamic problems. Today, there are several dozen RANS-LES models in use. A huge number of works are devoted to their further improvement and development. The most common method has become the detached eddy simulation (DES) method. This demonstrates the positive aspects of the idea underlying hybrid models. How- ever, even today, there is no complete satisfaction with the existing models. The construction of a mathematical model of turbulent flow requires further study of the physical characteristics of the for- mation of local unsteady characteristics of turbulent flows. When solving aerodynamic problems numerically using Reynolds-averaged Navier-Stokes equations, it is not the differ- ential equations themselves that are solved, but their finite difference analogues. It is necessary to correctly apply the physical laws of conservation of mass, momentum, and energy. This is a difficult task for mesh methods. In this work, for the numerical solution of the problem of calculating the characteristics of turbulent flow around a ground vehicle, a model of viscous compressible gas flow is chosen, which is described by Reynolds-averaged Navier-Stokes equations. A multi-block approach and a curvilinear coordinate system are used. To close the Reynolds-centered Navier-Stokes equations, the DES method was chosen, which is a further development of the Spalart-Allmaras turbulence model in the implementation of isolated vortices. To conduct the research, an appropriate methodol- ogy was developed, algorithms were constructed, and a software package was written in the Fortran-95 programming language. Calculations were performed for turbulent flow around a high-speed transport vehicle with a lifting body near a road structure. The distribution of isobars in the XOY plane of the calculation area, isochores in the XOY plane of the calculation area, isolines of the velocity vector component in the XOZ plane of the calculation area, and isolines of vorticity in the XOY plane of the calculation area were obtained.